2018
DOI: 10.1111/aogs.13478
|View full text |Cite
|
Sign up to set email alerts
|

Interpregnancy interval and abnormally invasive placentation

Abstract: Introduction: The presence of a previous uterine scar is a strong risk factor for developing abnormally invasive placentation (AIP). We sought to determine whether a short interpregnancy interval predisposes to AIP. We hypothesized that a short interpregnancy interval after a previous cesarean delivery increases the risk of AIP in comparison with a longer interpregnancy interval. Material and methods: We performed a retrospective cohort study of women with a histological diagnosis of AIP and a history of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…1 They performed a retrospective cohort study evaluating the role of a short interpregnancy interval (IPI) in the occurrence of abnormal invasive placentation (AIP). 1 They performed a retrospective cohort study evaluating the role of a short interpregnancy interval (IPI) in the occurrence of abnormal invasive placentation (AIP).…”
Section: Abnormally Invasive Placentation In Cohort Studies-refining mentioning
confidence: 99%
See 1 more Smart Citation
“…1 They performed a retrospective cohort study evaluating the role of a short interpregnancy interval (IPI) in the occurrence of abnormal invasive placentation (AIP). 1 They performed a retrospective cohort study evaluating the role of a short interpregnancy interval (IPI) in the occurrence of abnormal invasive placentation (AIP).…”
Section: Abnormally Invasive Placentation In Cohort Studies-refining mentioning
confidence: 99%
“…
Sir,We read the original research by Martimucci et al with great interest. 1 They performed a retrospective cohort study evaluating the role of a short interpregnancy interval (IPI) in the occurrence of abnormal invasive placentation (AIP). In their study, 67 women were included in the study group and 86 in the control group.
…”
mentioning
confidence: 99%
“…We estimated that a sample size (with continuity correction) of 214 with a 1 : 1 case to control ratio (107 cases and 107 controls) would allow us to accept a two-tailed alpha error of 0.05 and beta error (type II error) of 0.10 at 90% power using the prevalence of placenta previa of 26.7% [ 15 ] for women with short IPI following previous cesarean section and an expected decrease of 10.0% in the controls with normal IPI. However, we recruited 139 participants in each of the case and control groups to account for possible loss to follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…1 In the letter by Levin & Rottenstreich 2 the authors wrote that a well-designed study should include a large sample size to achieve a high enough power, referencing Eshkoli et al 3 That paper had 139 women as the study group with clinically diagnosed placenta accreta, and 34 000 women which included all the cesarean deliveries during that time period that were not associated with placenta accreta. 1 In the letter by Levin & Rottenstreich 2 the authors wrote that a well-designed study should include a large sample size to achieve a high enough power, referencing Eshkoli et al 3 That paper had 139 women as the study group with clinically diagnosed placenta accreta, and 34 000 women which included all the cesarean deliveries during that time period that were not associated with placenta accreta.…”
Section: Sirmentioning
confidence: 99%
“…Thank you for your comments on our manuscript. 1 In the letter by Levin & Rottenstreich 2 the authors wrote that a well-designed study should include a large sample size to achieve a high enough power, referencing Eshkoli et al 3 That paper had 139 women as the study group with clinically diagnosed placenta accreta, and 34 000 women which included all the cesarean deliveries during that time period that were not associated with placenta accreta. Eshkoli et al's paper sought to evaluate risk factors for placenta accreta and found that placenta previa is an independent risk factor.…”
Section: Sirmentioning
confidence: 99%